Penerapan Model 4D dalam Pengembangan Modul Layanan Bimbingan dan Konseling pada Siswa Sekolah Dasar - Anggun Shaqhira; Hadiarni (Yayasan Dinamika Ilmu Banyuwangi, 2025)
Psychological violence among elementary school students is a problem that affects the emotional, social, and academic development of students. One preventive measure that can be taken is through guidance and counseling services supported by educational media that are appropriate for the characteristics of students. This study aims to develop a poster-based guidance and counseling service module as an educational tool for the prevention of psychological violence among elementary school students. The research method used is Research and Development (R&D) by adapting the Four-D (4D) model, which includes the define, design, and develop stages. Data collection techniques were carried out through the distribution of needs instruments and expert validation sheets. Data analysis used quantitative descriptive statistics and Kendall's W concordance test to determine the level of agreement among assessors. The results showed that the developed module was in the highly feasible category based on expert assessment. Thus, the poster-based guidance and counseling service module has the potential to be an effective supporting medium in efforts to prevent psychological violence in elementary schools.